2001
DOI: 10.1152/ajpcell.2001.280.1.c90
|View full text |Cite
|
Sign up to set email alerts
|

A role for PYK2 in regulation of ERK1/2 MAP kinases and PI 3-kinase by ANG II in vascular smooth muscle

Abstract: Abnormal vascular smooth muscle cell (VSMC) growth plays a key role in the pathogenesis of hypertension and atherosclerosis. Angiotensin II (ANG II) elicits a hypertrophic growth response characterized by an increase in protein synthesis without cell proliferation. The present study investigated the role of the nonreceptor tyrosine kinase PYK2 in the regulation of ANG II-induced signaling pathways that mediate VSMC growth. Using coimmunoprecipitation analysis, the role of PYK2 as an upstream regulator of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 29 publications
4
106
0
1
Order By: Relevance
“…Several reports have shown that activation of Pyk2 was necessary for the activation of ERKs and/or SAPKs in different cell lines and in response to various stimuli (47)(48)(49)(50)(51)(52). Thus, it was of interest to determine whether the inhibition by s-FKN of MCP-1-induced p38/SAPK2 activity, which leads to the abrogation of MCP-1-induced chemotaxis of MonoMac6 cells, was associated with an inhibition of Pyk2 activity.…”
Section: S-fkn Abrogates the Mcp-1-induced Activation Of Pyk2 In Monomentioning
confidence: 99%
“…Several reports have shown that activation of Pyk2 was necessary for the activation of ERKs and/or SAPKs in different cell lines and in response to various stimuli (47)(48)(49)(50)(51)(52). Thus, it was of interest to determine whether the inhibition by s-FKN of MCP-1-induced p38/SAPK2 activity, which leads to the abrogation of MCP-1-induced chemotaxis of MonoMac6 cells, was associated with an inhibition of Pyk2 activity.…”
Section: S-fkn Abrogates the Mcp-1-induced Activation Of Pyk2 In Monomentioning
confidence: 99%
“…In this context, Ca 2 þ -dependent proline-rich tyrosine kinase Pyk2 has been identified as an intermediate in [Ca 2 þ ] i -mediated ERK activation in a variety of different cells (Lev et al, 1995;Rocic et al, 2001). Pyk2 is closely related to focal adhesion kinase (FAK) and highly expressed in the central nervous system, cells derived from hematopoietic lineages as well as in liver, renal epithelial and vascular smooth muscle cells (Schlaepfer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Pyk2 lacks Src homology 2 and 3 (SH2 and SH3) domains but contains sequences capable of binding to SH2 and SH3 domains of other proteins, including Src family kinases, the adaptor protein Grb2 (14,26), and the focal adhesion proteins paxillin (17,19,22,28,46) and p130CAS (43). In particular, tyrosine-402 (Tyr-402) has been identified as the key site for Pyk2 autophosphorylation and activation (14), with other tyrosine sites contributing to subsequent transphosphorylation and enhanced kinase activity (27,50).…”
mentioning
confidence: 99%